A Case of Adrenergic Crisis Caused by Spontaneous Rupture of Cystic Pheochromocytoma - Miura, Kenji (Hinyokika kiyo. Acta urologica Japonica, 2015)
Pheochromocytoma crisis is a life-threatening situation. Herein we report a case of catecholamineinduced crisis caused by the rupture of cystic pheochromocytoma. A 76-year-old man with hypertension was referred to our hospital because of a cystic tumor in the retroperitoneal space adjacent to the aorta, which was suspicious of pheochromocytoma. Two days after admission, lower abdominal pain suddenly appeared, followed by hypertension with systolic pressure of 260 mmHg. Computed tomography revealed that the cystic tumor was ruptured spontaneously, leading to diagnosis of pheochromocytoma crisis. His blood pressure was successfully managed by medical treatment and he could recover from crisis. After adequate medical preparation by an α-adrenergic blocker, the tumor was successfully removed by laparoscopy, though the adhesion around the tumor was severe. To our knowledge adrenergic crisis caused by spontaneous rupture of cystic pheochromocytoma is rare, but we have to keep in mind that cystic pheochromocytoma can cause life-threatening crisis by the release of catecholamine due to rupture